2009
DOI: 10.1007/s00535-009-0099-6
|View full text |Cite
|
Sign up to set email alerts
|

TIPS for refractory ascites: a single-centre experience

Abstract: The results of our study confirm the efficacy of TIPS for refractory ascites. The use of narrow-diameter dilatation without aiming at lowering the PPG below a certain threshold might simplify the procedure and the follow-up for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 15 publications
(28 reference statements)
1
33
0
Order By: Relevance
“…Comment: Two RCTS [32,33] and a meta-analysis [29] of six studies (one prospective and five retrospective) comparing TIPS placement with PTFE-covered stents and bare stents for portal hypertension related complications showed that the covered stent was superior in terms of shunt dysfunction (HR = 0.28; 95% CI 0.20-0.35).…”
Section: Which Types Of Device Are Available For Tips?mentioning
confidence: 99%
See 2 more Smart Citations
“…Comment: Two RCTS [32,33] and a meta-analysis [29] of six studies (one prospective and five retrospective) comparing TIPS placement with PTFE-covered stents and bare stents for portal hypertension related complications showed that the covered stent was superior in terms of shunt dysfunction (HR = 0.28; 95% CI 0.20-0.35).…”
Section: Which Types Of Device Are Available For Tips?mentioning
confidence: 99%
“…A step-wise procedure based on the progressive dilation of 10-mm diameter covered stents by using balloon catheters of increasing diameter might be used. The extent of dilation can be considered acceptable when the target PPG is reached (in case of variceal bleeding) (1a, A) [14] or an adequate clinical response is obtained (in case of refractory/recidivant ascites) (4, C) [14,25,31,32]. 1.6b There is not enough evidence to support the use of 10-mm rather than 8-mm nominal diameter PTFE-covered stents aiming to achieve a better control of portal hypertension complications (5, D) [33,34].…”
Section: Which Types Of Device Are Available For Tips?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several metaanalyses based on RCTs revealed that TIPS is superior in controlling ascites than LVP, although it causes hepatic encephalopathy more frequently [167][168][169][170]. The use of narrow-diameter dilation by TIPS decreased the incidence of severe hepatic encephalopathy [171]. The introduction of a covered stent offers better symptomatic control and overall survival, especially in patients with a MELD score of less than 16 at the baseline [172,173].…”
Section: Cq: Is Albumin Infusion Effective For Treatment Of Cirrhoticmentioning
confidence: 99%
“…Despite these advances, HE remains a pertinent post-procedural complication as portosystemic shunt physiology can trigger or worsen HE [1,2,8] . New or progressive post-TIPS HE of any severity has been shown to occur in 5%-35% of patients, while severe post-TIPS HE that does not respond to medical management and requires TIPS reduction or occlusion, occurs in up to 7% of patients [3,10,15,16] . Given the potential conflicting relationship between portal decompression and HE, efforts have been made to develop techniques to balance the desired therapeutic effect while minimizing over-shunting [3,17] .…”
Section: Introductionmentioning
confidence: 99%